Demonstration of a high extinction ratio TiN-based TM-pass waveguide polarize - Zhao, Zhuan; Santi, Giovanni; Corso, Alain Jody; Pelizzo, Maria-Guglielmina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
A high extinction ratio transverse magnetic (TM)-pass plasmonic waveguide polarizer has been designed and optimized. This device exploits two parallel TiN strips embedded in a silicon dioxide cladding to cut off the transverse electric (TE) polarization state, which is either reflected or absorbed, while the TM mode can pass through the main silicon waveguide with significant low losses. Given a device of 5 µm length, an extinction ratio as high as 60.7 dB and an insertion loss of 2.23 dB were achieved at the target wavelength of 1.55 µm. To our knowledge, this extinction ratio is one of the highest values ever reported. In the wavelength of 1.45–1.59 µm, the proposed device provides an optical bandwidth of 140 nm for an extinction ratio more than 30 dB and an insertion loss less than 3 dB. This device is relatively simple and is easier to be fabricated than other architectures that are found in the literature
Optica Applicata, Vol. 52, 2022, nr 4, s. 585-598
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; plasmonic waveguide polarizer; extinction ratio; insertion loss; broadband